Pemikiran Musa’id Ibn Sulaiman Ath-Thayyar Tentang I'jaz 'Ilmi - Shohib Khoiri; Syed Mohammad Chaedar; Muhammad Yusry Affandy Bin Md Isa; Nusairah Binti Ramli (Academic Inspired Network (AIN), 2024)
Volume: 8 Issues: 59 [December, 2023] pp. 179 - 189